A Wager on Global Food Prices 2001-2020: Who Won and What Does it Mean?. (14th December 2021) - Becker, Stan; Lam, David
Abstract : This paper presents the results of a 2011 wager between Stan Becker and David Lam about the trajectory of world food prices for the period 2011–2020 versus the period 2002–2010. The wager was a response to Lam's 2011 presidential address to the Population Association of America, which showed that many health and socio-demographic indicators had improved over the previous fifty years, in spite of the addition of four billion people to the world's population. Lam lost the wager, with the Food and Agriculture Organization's price index for five food groups averaging about twenty per cent higher for 2011–2020 than for 2001–2010. Becker and Lam discuss the background of the wager, give their differing interpretations of the outcome and discuss future trends in population, food production and food prices. Lam gives a more optimistic perspective on future trends, while Becker raises concerns about rapid degradation of planetary ecosystems, species loss and global warming.